High Entrepreneurship, Leadership, and Professionalism (HELP): A New Resource for Workers in the 21st Century - Palazzeschi, Letizia; Bucci, Ornella; Fabio, Annamaria Di (Frontiers in Psychology, 2018)
World of work in the 21st century is characterized by instability, insecurity, and continuous change. To face these challenges of the post-modern era, workers are required to use their personal resources. A new construct called high entrepreneurship, leadership and professionalism (HELP) is a preventive resource that helps maintain, improve, and find work in uncertain or dynamic conditions. This study aims to examine the personality correlates of HELP in Italian workers and identify different clusters based on HELP and other variables, such as workplace relational civility and flourishing. To this end, the following instruments were administered to 204 Italian workers: the HELP questionnaire, the Big Five Questionnaire, the Workplace Relational Civility Scale, and the Flourishing Scale. The personality correlates of HELP underscored the role of conscientiousness (and its subdimension perseverance) and extraversion (and its subdimension dominance). The cluster analysis identified three clusters characterized by high, average, and low HELP scores. Participants in the first cluster with high HELP scores appeared to possess higher perseverance, dominance, workplace relational civility, especially readiness, and higher flourishing than those in the other two groups. The present results can open new opportunities for future research and interventions in a primary prevention perspective to foster resources for workers and healthy organizations in the 21st century.